(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2019)
Abstract – Dall’invenzione del Web, sempre più studiosi si chiedono in quale misura le nuove modalità di scrittura e fruizione delle storie stiano modificando il modo in cui comunichiamo, ci relazioniamo, raccontiamo, e come influiscano sul nostro cervello. Questo contributo mette in luce come le modalità di produzione e pubblicazione dei racconti autobiografici e delle fanfiction all’interno del cyberspazio e la natura ‘convergente’ delle comunità online entro cui vengono creati renderebbero questo fenomeno culturale l’ambiente ideale per la costituzione di una identità ibrida, che contribuisce alla creazione di nuove modalità di formattazione del racconto. Dall’analisi a campione di blog, microblog e fanfiction emerge un nuovo format digitale, che si allontana sempre più dal tradizionale impianto narrativo occidentale. Parole chiave – format narrativi; storytelling digitale; identità narrativa; fanfiction; blog; microblog. Abstract – From the invention of the Web more and more scholars are asking themselves how the new ways of writing and using stories are changing the way we communicate, relate, tell, and how they affect our brain. This article highlights how the methods of production and publication of weblog, microblog and fanfiction within cyberspace and the ‘convergent’ nature of the fandom communities within which they are created would make this cultural phenomenon the ideal environment for the creation of a hybrid identity. The latter opens new horizons in terms of narrative format. The sample analysis of different blog, microblog and fanfics shows the development of a new narrative format. As a result, this format moves away from the traditional Western narrative format. Keywords – narrative format; digital storytelling; narrative identity; fanfiction; blog; microblog.